On-line pre-concentration of arsenic compounds by dynamic ph junction-capillary electrophoresis - Irwan, Zildawarni (2008)
Capillary electrophoresis (CE) with ultraviolet (UV) detection suffers from a poor concentration sensitivity resulting in a significant obstacle for analysis of part per billion levels of analytes in real samples. Therefore, there is a need to develop a simple yet effective pre-concentration method to enhance concentration sensitivity of trace level analytes in real samples for CE analysis. In this research, dynamic pH junction as an on-line pre-concentration method was employed for the determination of the animal feed additive roxarsone (3-nitro-4-hydroxyphenylarsonic acid) and four of its most possible degradation products (arsenite, arsenate, monomethylarsonic acid and dimethylarsinic acid). Phenylarsonic acid was included as an internal standard. The separation was conducted in a fused-silica capillary using 15 mM Na2HPO4-Na3PO4 buffer, pH 10.6 and 15 mM CH3COOH, pH 3.5 sample matrix at a voltage of 25 kV. Arsenite, arsenate, monomethylarsonic acid and dimethylarsinic acid were detected at 192 nm wavelength while phenylarsonic acid and roxarsone were detected at 254 nm wavelength. This on-line pre-concentration method, compared to the conventional capillary zone electrophoresis (CZE) method, resulted in an increased detection response of up to 51-fold in terms of peak height of arsenic compounds. The lower limit of detections (LODs) for the arsenic compounds obtained were in the range of 0.34-1.93 µg/L in comparison with conventional capillary zone electrophoresis with the LODs in the range of 140-293 µg/L. Reproducibility of the analytes in terms of migration time was in the range of 1.96-5.37% RSD. The proposed method was applied to the determination of roxarsone in chicken manure and soil samples. Roxarsone was extracted with distilled water and the analyte was then cleaned up using solid-phase extraction technique which uses a high anion exchange cartridge (HAX) as an off-line sample pre-concentration and sample clean up as well as C18 cartridge for further sample clean up mainly to remove organic contaminant before analysis using dynamic pH junction-CE. Recovery of the roxarsone obtained was 70 ± 1% for chicken manure samples and 72 ± 2% for soil samples.